2021
DOI: 10.1002/anie.202113443
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Synthesis of Poly(silylether)s: Access to Degradable Polymers from Renewable Resources

Abstract: The design of new materials with tunable properties and intrinsic recyclability, derived from biomass under mild conditions, stands as a gold standard in polymer chemistry. Reported herein are platinum complexes which catalyze the formation of poly(silylether)s (PSEs) at low catalyst loadings. These polymers are directly obtained from dual-functional biobased building blocks such as 5-hydroxymethylfurfural (HMF) or vanillin, coupled with various dihydrosilanes. Access to different types of copolymer architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 119 publications
3
19
0
Order By: Relevance
“…Following this idea, mild degradability is anticipated if PU networks could be incorporated with hydrolyzable bonds in response to mild conditions. Among cleavable linkages, silaketal, usually applied as the protector for the hydroxyl group, is adequate to achieve controllable bond formation and fragmentation under different acid/base environments. In general, silaketal is usually prepared from the condensation reaction between chloroalkylsilane and hydroxyl groups in the presence of a Lewis base, and the silaketal linkages can be further hydrolyzed under mild acidic conditions . It is noteworthy that the reaction activity of silaketal hydrolysis varies concomitantly with the change of alkyl substituents on silicon atoms, and the acidity of the environment also dominates the hydrolysis rate. , In that case, introducing silaketal linkages with different alkyl substituents into thermosetting PU materials will be a feasible approach to regulate the degradation rate as well as accomplish moderate recyclization …”
mentioning
confidence: 99%
“…Following this idea, mild degradability is anticipated if PU networks could be incorporated with hydrolyzable bonds in response to mild conditions. Among cleavable linkages, silaketal, usually applied as the protector for the hydroxyl group, is adequate to achieve controllable bond formation and fragmentation under different acid/base environments. In general, silaketal is usually prepared from the condensation reaction between chloroalkylsilane and hydroxyl groups in the presence of a Lewis base, and the silaketal linkages can be further hydrolyzed under mild acidic conditions . It is noteworthy that the reaction activity of silaketal hydrolysis varies concomitantly with the change of alkyl substituents on silicon atoms, and the acidity of the environment also dominates the hydrolysis rate. , In that case, introducing silaketal linkages with different alkyl substituents into thermosetting PU materials will be a feasible approach to regulate the degradation rate as well as accomplish moderate recyclization …”
mentioning
confidence: 99%
“…An alternative attractive pathway to BHMF-based polyesters from FDCA was recently introduced by Thomas and Gauvin relying on one-pot catalysis [45,46]. Thus, an esterification-hydrogenation-copolymerization sequence was developed using molecular catalysis, enabling the one-pot transformation of FDCA into the desired polyesters.…”
Section: Bhmf-based Polymer Productionmentioning
confidence: 99%
“…Methanolysis is one of the most commonly used protocols to investigate the degradation behavior of polymers. 64 However, it has been widely reported that polycarbonates are resistant to methanolysis in the absence of catalysts. 65,66 Although large amounts of concentrated acids or bases can act as catalysts, 51 a substantial drawback of this approach is the generation of large quantities of inorganic salts and aqueous wastes.…”
Section: Degradability and Recyclability Studiesmentioning
confidence: 99%